Peran Mahasiswa dalam Pengenalan Bahan Ajar Digital Berbasis Website untuk Meningkatkan Keterampilan Bahasa Indonesia Siswa MI di Kota Palangka Raya - Fatimatu Zahra; Sifana Dewi; Aulia Rahmah Ariani; Zaitun Qomariah; Rahmad (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2025)
This Community Service (PKM) activity aims to overcome the problem of low Indonesian language skills of students at MI/SD Palangka Raya City, which is caused by the lack of interactive teaching materials. This study developed website-based digital teaching materials to increase student motivation and involvement in the learning process. The methods used include needs analysis, learning media design, and training in the use of teaching materials for students and teachers. Quantitative results showed an increase in the average student score from 72.8 in the pretest to 88.2 in the posttest, with 95% of material experts assessing the teaching materials as very suitable for use. In addition, positive feedback from teachers and students reflects increased motivation and active participation in learning. This PKM activity is expected to be an innovative model in basic education, providing a positive contribution to the quality of Indonesian language learning at the elementary school level